The neighborhood walk: introducing first-year medical students to social determinants of health in underserved neighborhoods - Tien C. Nguyen; Lilly W. Tang; Emma Bryant; Awa S. Jobe; Amy J. Yu; Yui Sugiura; Thuy Bui (BMC Medical Education, 2025)
Abstract Background Social determinants of health (SDoH) contribute to up to 80% of an individual’s health, underscoring its importance in medical education. Research has shown that community exposure and engagement during undergraduate medical education increases the likelihood of students working in underserved areas in the future. Given the limited research on the feasibility and educational effects of SDoH experiences implemented at the early stages of medical education, this study presents a unique perspective on an interactive learning opportunity during the preclinical curriculum. The purpose of this study is to evaluate the educational impact of an immersive social determinants of health learning intervention for first-year medical students. Methods First year medical students visited one of five underserved neighborhoods in Pittsburgh during Orientation Week. Students received materials about neighborhoods and community engagement etiquette prior to their visit. Visits spanned four hours with two groups of approximately 15 students for each neighborhood, led by at least one faculty member and two student facilitators. Students visited two to four community organizations in each neighborhood and participated in a debrief session. Students completed a feedback survey, and results were analyzed with Chi-square Test of Independence (p < 0.05). Results The survey response rate was 58.2%. Students ranked the intervention as “Excellent” (77%), “Above Average” (14%), and “Good” (7%). When asked to rate the comfortability of helping patients obtain community resources on a scale of 1–5, 64.3% of students rated 4 or above. Similarly, 91.6% of students rated 4 or above when asked about knowledge of available resources in their neighborhood. The major learning outcomes from students were richness of community resources/history (35.7%), food insecurity (26.2%), and dissipation of previous stigma (23.8%). There was a significant association between growing up in Pittsburgh and self-rating of comfortableness with helping patients obtain community resources (p = 0.02). Students who completed pre-visit materials were more likely to rate the materials (p < 0.01) and debrief session as helpful (p < 0.01). Conclusions Prior exposure to and information about communities was found to enhance the neighborhood learning experience. This initiative demonstrates the benefit of early engagement with community resources and neighborhood-based health disparities in undergraduate medical education.